THE USE OF PEER FEEDBACK STRATEGY TO MOTIVATE STUDENTS IN NARRATIVE TEXT WRITING (English Education Journal, 2012)
Penelitian ini bertujuan untuk untuk (1) menemukan masalah siswa pada penulisan teks naratif (2)menggambarkan implementasi dari strategi pair feed back pada penulisan teks naratif (3) mengetahui apakah strategi peer feedback dapat memotivasi siswa untuk menulis teks naratif (4) mengetahui apakah meningkatkan teks naratif siswa. Subjek penelitian ini adalah siswa kelas XI IA2 SMA Futuhiyyah Demak. Penelitian ini merupakan kolaboratif action research. Instrumen penelitan ini adalah observasi, interview, kuisioner, dan tes tertulis. Penelitian ini terdiri dari 3 cycle dan setiap cycle dilaksanakan pada 4 pertemuan. Hasil menunjukan bahwa siswa memiliki motivasi yang rendah sebelum penelitian dilaksanakan. Setaelah diadakan penelitian, motivasi siswa meningkat, mereka dapat bekerja bersama dan berpartisipasi selama kelas. Beberapa siswa masih memiliki motivasi yang rendah dalam penentuan tujuan personal, learner-centered, kreatifitas, dan refleksi diri. Dari cycle yang kedua, implementasi dari strategi peer feedback dapat meningkatkan motivasi dalam cooperative learning.This study was aimed at (1) finding out the problems faced by students in narrative texts writing, (2) describing the implementation of peer feedback strategy in narrative texts writing, (3) knowing whether peer feedback strategy can motivate students to write narrative texts, (4) knowing whether peer feedback strategy can improve students’ narrative texts. The subject of this study was the eleventh grade students of XI IPA 2 of SMU Futuhiyyah Demak. The research design of this study was collaborative action research. The instruments of this study were observation, interview, questionnaire, and writing test. This study consisted of three cycles and each cycle consisted of three meetings. The findings showed that the students had low motivation before the actions were implemented. From the result of the first cycle, the students’ motivation increased. They could work in pair and participate during the writing class. Some students still had low motivation in the aspect of personal goal-setting, learner-centered, creativity, and self-diagnosis. From the second cycle, the implementation of peer feedbacks strategy could generate students’ motivation in the aspect of cooperative learning and peer evaluation. The students were not confused with the activities in peer feedback strategy. They knew what they should do in peer feedback strategy.